Relationship between the business environment and business strategy types: evidence in Peruvian companies - Ostos, Jhony (2016)
Various authors hold that the business environment is a variable with influence on corporate strategic decision-making. However, research does not delve into the influence of various types of business strategies. This empirical study, based on a survey of 99 service companies has the aim to review the influence of the business environment on the various types of business strategies. Additionally it examines organization characteristics, as a moderating variable of the relationship between environmental variables and strategy types. Our analysis reviewed two major components of the environment: complexity and uncertainty, and their interrelations with three types of business strategies: prospectors, analyzers and defenders. Statistical outcomes show that a complex business environment impacts the three types of strategy: prospectors, analyzers and defenders, while an uncertain environment only impacts companies enforcing prospectors’ strategies. These findings show not all companies consider the uncertain environment when designing their business strategies. It was also found that organizational characteristics do not moderate the relationship between both variables.